A new species of climbing Chamaedorea (Arecaceae) from Chiapas, Mexico - Pérez-Farrera, Miguel Angel; Gutiérrez-Ortega, José Said; Hodel, Donald R.; Villar-Morales, Diego; Santos-Hernández, Nancy Gabriela; Martínez-Camilo, Rubén (Phytotaxa, 2021)
Chamaedorea tacanensis (Arecaceae), a new species from the Tacaná Volcano Biosphere Reserve, Chiapas, Mexico, is described based on morphological and phylogenetic data. It is morphologically similar to C. elatior, the only other climbing species in the genus. However, C. tacanensis is distinguished by having linear pinnae (lanceolate in C. elatior), petioles emerging glaucous (glabrous in C. elatior), and longer rachises, blades and peduncles than C. elatior. Also, C. tacanensis has pinnate-leaved seedlings and juveniles, whereas they are simple or bifid in C. elatior. The two taxa form separate monophyletic groups. Geographically, C. tacanensis is found in tropical montane cloud forests of the Pacific slope whereas C. elatior mostly occurs in lowland tropical forests of the Atlantic slope. Chamaedorea tacanensis has been recorded in only three localities: two in the Tacaná Volcano Biosphere Reserve, Mexico, and one in San Marcos, Guatemala. Further floristic studies in surrounding areas might better clarify the geographic distribution range of this species.